RATIO PENGENCERAN SPERMA TERHADAP MOTILITAS SPERMATOZOA, FERTILITAS DAN DAYA TETAS IKAN LELE (Clarias sp.) - Adipu, Yulianty; Sinjal, Hengky J; Watung, Juliaan (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2011)
This study was aimed to determine the effect of the dilution ratio of sperm with optimal NaCl and fructose on the motility of the catfish, Clarias sp., spermatozoa, fertility and hatchability of eggs. Catfish used in this study consisted of one parent pairs (male and female weight of 1000 grams weight of 1500 g). NaCl and fructose solution were diluted with aquabidest. The observation was conducted on the motility of spermatozoa, fertility and hatchability of eggs. The experimental design used completely randomized design (CRD). Dilution ratio is 1: 0, 1, 20, 1: 40, 1; 60, 1: 80, and 1: 100 with replicated 3 times. Observations were carried out soon after the sperm mixed with diluents. Fertility occurred 12 hours after fertilization. Egg hatchability was observed after fertilization. The results showed that the ratio of dilution gave significant effect on the sperm motility, fertility and hatchability of the eggs. This research found that the dilution ratio 1: 60 was the best treatment with the average sperm motility of 96. 66%, fertility of 71, 66 5% and egg hatchability of 70%.